Quality of the ISO 9000 series of standards-perceptions of quality management experts. Issue 4 (6th August 2021) - Rogala, Piotr; Wawak, Sławomir
Abstract : Purpose: The authors of this study, who adopted a holistic view of the international organization for standardization (ISO) 9000 series of standards, aimed to evaluate the current status of the standards within the framework of the quality movement. Specifically, the evaluation covered two dimensions, i.e. the significance of the content included in the standards and the quality of the standards' elaboration, which encompasses such issues as, for instance, their correctness, relevance to current trends in quality management, comprehensibility, etc. Design/methodology/approach: The paper is based on a review of the scientific literature, analysis of the current and all previous versions of the international standards and the results of a survey, through which data were collected from 73 quality management experts from 17 different countries. To evaluate the results, an importance-performance analysis was performed. Findings: As the results of the research demonstrated, experts in quality management have accepted the ISO 9000 standards series. However, this positive view refers mainly to the very idea of developing quality management standards and these standard's content structure (components included in them). Study participants assigned a low rating to the quality of the standards' elaboration. Therefore, improving the following aspects of the standards is essential: definitions, guidelines explaining the requirements for a quality management system, self-assessment tools and guidelines concerning quality management concerning chosen forms of activity. Research limitations/implications: The research described here in has both practical and social implications. First, it delineates the direction needed to improve standardizations, whose use need not be strictly limited to quality management but can be successfully used to improve the standards in other areas of management. Therefore, the conclusions of this research directly contribute to increasing both the effectiveness and the quality of the standard organizations. The significant consequences of this research for managers are the identification of ISO 9000 components which they will find are the most useful. Practical implications: The research described herein has both practical and social implications. First, it delineates the direction needed to improve standardizations, whose use need not be strictly limited to quality management. However, it can be successfully used to improve the standards in other areas of management. Therefore, the conclusions of this research directly contribute to increasing both the effectiveness and the quality of the standard organizations. The significant consequences of this research for managers are the identification of ISO 9000 components, which they will find are the most useful. Originality/value: Most research treats ISO 9000 standards as a benchmark for their studies on quality management systems implemented in organizations. The standards themselves are rarely the subject of a study, and so this paper fills a gap in the research and provides insights into desired directions for standards improvement.